As relações entre cognição e afeto, escola e família na sociabilidade e aprendizagem de adolescentes da atualidade: uma análise à luz da pedagogia terapêutica de João dos Santos - Moura, Maíra Maia de (2019)
The present study deals with the learning and sociability of adolescents in the present day in the family and in the school. In order to do so, it analyzes concepts of adolescence, learning, family, school and therapeutic pedagogy, through a bibliographical survey selected, analytically based, above all, the Pedagogical Therapy or Psychopedagogy of João dos Santos, which draws attention to the importance of childhood and an education integrated by several agents, that considers responsible of the social education of children and young people. It carries out a qualitative empirical study, together with a group of adolescents, family and educators, through semi-structured interviews and content analysis of speeches, from which thematic categories are extracted that reveal the problematic of learning and sociability characteristic of adolescence as phase of the life where the definition of the social identity of subjects occurs. It presents as results the dilemmas and difficulties typical of adolescence in the present day, characterized by a certain lack of horizons of happiness in the face of a society in which the education of the youth is in disagreement with the desired future amid fears, desires and frustrations . It demonstrates the relevance and appropriateness of the therapeutic pedagogy developed by João dos Santos as a presupposition and conceptual support for the understanding of the problematic studied for revealing procedures favorable to the social education of children and young people who have in the integrated and solidarity action of the family, school and society the best way to a pedagogical approach to reparation.